1978
DOI: 10.1111/j.1744-313x.1978.tb00667.x
|View full text |Cite
|
Sign up to set email alerts
|

A WEAK HUMAN MLR LOCUS MAPPING AT THE RIGHT OF A CROSSING‐OVER BETWEEN HLA‐D, Bf AND GLO

Abstract: SUMMARY An unexpected MLR reaction has been observed between three HLA‐identical sibs; it consists of a bidirectional positive MLR between identical female twins and a sister. No argument for a lymphoid mosaic could be found, although twins were frequent in the family; similary no HLA‐A/B or HLA‐B/D recombinant could be demonstrated. The MLR, although weak, was highly reproducible. PLTs could be raised between the sibs, without an apparent segregation in this family nor in five other families, but such PLTs di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 29 publications
(13 reference statements)
1
24
0
Order By: Relevance
“…Definitive Assignment of the HAfi Gene(s) to the SB Region. Previous family studies were reported to show recombination between SB and DR (3)(4)(5)(6)(7)(8). In family Fa(3), a recombination divided the HLA-D region into two subregions, a Fig.…”
Section: Pst T Trpnacg Rkagctk Egcggccteaagap0agtactggpcagccagaagacatmentioning
confidence: 95%
See 1 more Smart Citation
“…Definitive Assignment of the HAfi Gene(s) to the SB Region. Previous family studies were reported to show recombination between SB and DR (3)(4)(5)(6)(7)(8). In family Fa(3), a recombination divided the HLA-D region into two subregions, a Fig.…”
Section: Pst T Trpnacg Rkagctk Egcggccteaagap0agtactggpcagccagaagacatmentioning
confidence: 95%
“…The study of recombinant families in which positive MLR was detected between cells of genotypically DR,DC/MT-identical individuals allowed the division of the D region, between DR and GLO, into two subregions. These subregions were separated by recombination into a telomericregion coding for the DR and DC/ MT antigens and a centromeric region coding for a new segregant series called SB (3)(4)(5)(6)(7). Further analysis of informative.…”
Section: And 2)mentioning
confidence: 99%
“…The DP locus of the HLA class II system was first described in 1978 as a target of alloreactive T-cell responses identified in secondary mixed lymphocyte cultures. 2 Due to the scarce availability of specific antisera, the gene products of the HLA-DP locus remained poorly characterized for many years. Only the advent of molecular biology techniques for HLA typing allowed unraveling the full degree of HLA-DP polymorphism, with 20 and 106 HLA-DPA1 and DPB1 alleles, respectively, described to date.…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of leuko-agglutination by lymphocytotoxicity tests in 1964 [67] and the systematic analysis of antibodies formed in pregnancy have brought substantial progress in clinically applied HLA typing for class I antigens. The application of the PLT allowed the discrimination of six antigens HLA-DPwl -DPw6 [19,20]. In the late 1970s, sera from multiparous women were obtained with similar specificities as the MLC for HLA-D.…”
Section: Hla Typing Methodsmentioning
confidence: 99%
“…This locus became known as HLA-D. With the help of homozygous typing cells used in the MLC several alleles of this locus were defined [16]. The existence of a third HLA class II locus -named SB (now HLA-DP) -was demonstrated by the use of a secondary MLC, the primed lymphocyte test (PLT) [19,20]. These antigens were designated HLA-D related or HLA-DR. Further analysis of more sera succeeded in the discovery of the MB gene (now HLA-DQ) [18].…”
Section: History Of Hlamentioning
confidence: 99%